Association between PTPN22 C1858T polymorphism and juvenile idiopathic arthritis: A meta‐analysis update with trial sequential analysis - Lee, Young Ho; Song, Gwan Gyu (International journal of immunogenetics, 2022)
Our aim was to determine whether protein tyrosine phosphatase nonreceptor 22 (PTPN22) C1858T polymorphism (rs2476601) is associated with susceptibility to juvenile idiopathic arthritis (JIA). MEDLINE and EMBASE databases were searched to identify articles in which PTPN22 C1858T polymorphism was reported to be identified in JIA patients and controls. A meta‐analysis was conducted to evaluate the association between PTPN22 C1858T polymorphism and RA using allelic contrast. Trial sequential analysis (TSA) was performed. Sixteen separate comparisons involving 5696 JIA patients and 9483 controls (a total of 15,179 subjects) were considered in this meta‐analysis. A meta‐analysis was performed with all JIA patients as well as JIA patients in each ethnic group. Meta‐analysis revealed an association between the T allele of PTPN22 C1858T polymorphism and JIA in all subjects (OR, 1.322; 95% CI, 1.233–1.418; p < .001). Analysis after stratification by ethnicity indicated that the T allele was significantly associated with JIA in the European population (OR, 1.312; 95% CI, 1.2211–1.410; p < .001). However, analysis performed in the non‐European population showed no significant association between the T allele and JIA. TSA indicated that the observed association between the PTPN22 polymorphism and JIA in all subjects and the European population is consistent with the existing evidence. This meta‐analysis confirms that PTPN22 C1858T polymorphism is associated with susceptibility to JIA in Europeans, and that no additional studies are needed to verify these results. However, current evidence in the non‐European population is insufficient, and further studies are warranted.